Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1989
DOI: 10.1148/radiology.170.3.2916027
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and determinants of adverse reactions induced by high-osmolality contrast media.

Abstract: To determine the frequency of and risk factors for adverse reactions to high-osmolality contrast media, the authors prospectively studied hospitalized patients undergoing cardiac catheterization. The authors also studied patients undergoing peripheral angiography and contrast material-enhanced computed tomography (CT) of the head or body who met at least one of the following criteria thought to increase the risk of adverse reactions: age of more than 60 years, diabetes, renal or liver disease, concurrent nephr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1989
1989
2009
2009

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…[30,31] Late reactions are reported with frequencies of between 8.7% and 70.0%, [34][35][36][37] and reports have also suggested that there is an increased frequency of late reaction with non-ionic dimeric CM compared to non-ionic monomeric CM. [31] The physiological background of late reaction is unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[30,31] Late reactions are reported with frequencies of between 8.7% and 70.0%, [34][35][36][37] and reports have also suggested that there is an increased frequency of late reaction with non-ionic dimeric CM compared to non-ionic monomeric CM. [31] The physiological background of late reaction is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…The use of aggressive hydration strategies before contrast infusion has been shown to be important in preventing CN. Severe complications in the high-risk patients, including adverse reactions of CM, [29][30][31] may be managed by hemodialysis. [28] In the past, non-ionic monomers and dimmers have both been shown to have a good safety profile in normal subjects.…”
Section: Introductionmentioning
confidence: 99%
“…Sepsis, through direct damage by bacterial toxins to renal tubules and impairment of circulation, has also been reported as a risk factor, as have hypertension, peripheral vascular disease, and atopic allergy [9,27,82].…”
Section: Sepsis and Othersmentioning
confidence: 99%
“…Recent experimental and clinical data show that much less tissue damage occurs following extravasation of non-ionic contrast medium [8]. Non-ionic contrast media are generally better tolerated [9][10][11]. Many patients do not accept the taste of Gastrografin (diatrizoate) when drinking a large volume.…”
Section: Introductionmentioning
confidence: 99%